2023
DOI: 10.1055/s-0043-1767751
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Healthy Sleep Habits in Adults with Diabetes Compared to Adults without Diabetes: A Reasoned Action Approach Elicitation Study

Abstract: Objective Sleep is part of a healthy lifestyle and in adults with diabetes, inadequate sleep is associated with risks of developing complications. The objective was to compare beliefs about healthy sleep habits (HSHs) in adults with versus without diabetes based on the Reasoned Action Approach. Methods A total of 56 adults with and 98 without diabetes answered open-ended questions regarding their beliefs about: avoiding screen use in bed; having a regular sleep schedule; or avoiding caffeine, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Sleep variability is associated with risk of T2D in adults (Rosique-Esteban et al, 2018 ), suggesting it might have an impact on glucose levels in adults with diabetes. As anticipated based on the results of our previous formative qualitative research (Vézina-Im et al, 2023 ), fewer adults with diabetes reported caffeine and alcohol consumption, and smoking cigarettes before bedtime. Similar numbers of adults with diabetes reported consuming caffeine (46.1%) and smoking cigarettes (8.6%) before bedtime compared with a study in which 45.0% and 9.2% of adults reported caffeine and nicotine consumption, respectively, before bedtime (Spadola et al, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Sleep variability is associated with risk of T2D in adults (Rosique-Esteban et al, 2018 ), suggesting it might have an impact on glucose levels in adults with diabetes. As anticipated based on the results of our previous formative qualitative research (Vézina-Im et al, 2023 ), fewer adults with diabetes reported caffeine and alcohol consumption, and smoking cigarettes before bedtime. Similar numbers of adults with diabetes reported consuming caffeine (46.1%) and smoking cigarettes (8.6%) before bedtime compared with a study in which 45.0% and 9.2% of adults reported caffeine and nicotine consumption, respectively, before bedtime (Spadola et al, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that the adoption of this HSH is not easy as adults with diabetes are faced with many barriers to overcome, which was also reflected in the low mean score for PBC to avoid screen use in bed. In our previous pilot study, adults with diabetes reported more barriers than facilitating factors (5 vs 2) compared to adults without diabetes (2 vs 3) for avoiding screen use in bed (Vézina-Im et al, 2023 ). Habit of using screens in bed was another significant psychosocial determinant of screen use in bed.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations